Primary bilateral ovarian Burkitt lymphoma; a rare issue in gynecologic oncology - Al-Maghrabi, Haneen (J Surg Case Rep, 2018)
We report a rare case of 42-year-old female patient with bilateral primary ovarian Burkitt lymphoma (BL). Primary BLs are rare ovarian oncology neoplasms. Only few cases are reported in English literature, most of them are presented in pediatric and young adult age groups. Rare cases are reported in adult females. Although BL is a rare primary ovarian neoplasm, it is very important to establish an accurate diagnosis as early as possible for therapeutic purposes.